Mental health of healthcare workers in times of pandemic - Castelo-Rivas, Walter Patricio (2023)
Objective. The aim of the study was to determine the influence of negative emotional states (stress, anxiety, and depression) on the mental health of health care workers in times of pandemic. Methods. This was a quantitative study of descriptive scope and cross-sectional design. The questionnaire consisted of 21 questions taken from the DASS 21 scale proposed by Lovibond and Lovibond (1995), and was applied to 229 health care workers in Santo Domingo de los Tsáchilas (Ecuador). Statistical analyses were carried out using Excel and SPSS 21. Results. Stress and anxiety were severe in health care workers over 31 years of age working in public and private hospitals; while anxiety was extremely severe in all study participants. Conclusions. The study is the first to present the results regarding the influence of negative emotional states in health care workers in Santo Domingo de los Tsáchilas and shows that stress, anxiety and depression were factors that had a considerable influence in times of pandemic.